Transformasi Pendekatan Guru Bahasa Arab MTsN 35 Jakarta dalam Menghadapi Kompleksitas Kurikulum Merdeka - Amalia, Rizky; Sativa, Oriza; Drazat, Zahidah; Maswani, Maswani (STAINI Press, 2025)
The transformation of Arabic language teachers' approaches has become an important study topic because the Merdeka Curriculum requires a shift in the learning paradigm to be more flexible, contextual, and student-centered, while Arabic language teaching still faces methodological and structural challenges. This study aims to investigate how Arabic language teachers adapt to the Merdeka Curriculum, particularly at MTsN 35 Jakarta. This data was collected by the author using descriptive qualitative techniques, including semi-structured interviews with one of the Arabic language teachers and literature studies on related policies. The findings of this research reflect a trend away from traditional methodologies and towards communicative, differentiated, and integrative approaches that cater to the current needs of learners. Teachers today are starting to use project-based learning, incorporate digital technology, and employ authentic holistic assessments. Contemporary educational theory and differentiation serve as the analytical foundation for this study. Some highlighted constraints include teacher readiness, inadequate infrastructure, lack of contextual teaching aids, and cultural hostility from some stakeholders. However, institutional support and ongoing training are crucial in advancing this shift. These findings emphasize the need for collaboration between teachers, schools, and communities in creating an adaptive, reflective, and relevant Arabic language learning environment to face challenges and implement the latest learning strategies in the 21st century. This work provides practical and theoretical contributions to the creation of Arabic language learning methodologies based on the Merdeka curriculum